2008
DOI: 10.1167/iovs.07-1041
|View full text |Cite
|
Sign up to set email alerts
|

Iron Regulates L-Cystine Uptake and Glutathione Levels in Lens Epithelial and Retinal Pigment Epithelial Cells by Its Effect on Cytosolic Aconitase

Abstract: These results demonstrate for the first time that iron regulates L-cystine uptake and the downstream production of GSH in two mammalian cell types. It is possible that the increase in intracellular antioxidant concentration induced by iron serves as a protective mechanism against the well-established capacity of iron to induce oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 38 publications
5
39
0
Order By: Relevance
“…18 In the present study, the amount of available iron in the LIP was increased by FHsiRNA transfection. This increase was confirmed by a decrease in the amount of 59 Fe found in ferritin (Fig.…”
Section: Cystine Uptake and Gsh Levels In Differentially Transfected supporting
confidence: 48%
See 1 more Smart Citation
“…18 In the present study, the amount of available iron in the LIP was increased by FHsiRNA transfection. This increase was confirmed by a decrease in the amount of 59 Fe found in ferritin (Fig.…”
Section: Cystine Uptake and Gsh Levels In Differentially Transfected supporting
confidence: 48%
“…17 The iron-regulated secretion of glutamate had downstream effects on cystine uptake by the cystine/glutamate antiporter and the levels of glutathione (GSH) in these cells. 18 The goal of the present study was to alter the ferritin H:L ratio with siRNA for each ferritin chain and to determine how these changes affect iron storage and availability, ferritin levels (including the kinetics of its synthesis and degradation), cystine uptake, GSH levels, HIF-1␣ translocation to the nucleus, and VEGF production in LECs.…”
mentioning
confidence: 99%
“…The same group [25] also uncovered a relationship where the level of iron transported into retinal-pigmented epithelial cells, neurons, or cultured lens epithelial cells would affect the cells' ability to manage ROS. Glutamate is also a precursor of the cellular reductant glutathione (GSH) and critically involved in making cysteine available for GSH synthesis via a glutamate/cystine antiporter.…”
Section: Neural Tissue and Related Cell Typesmentioning
confidence: 96%
“…Investigators in the McGahan lab showed that intracellular iron regulates the activity of system x c -in RPE cells via cytosolic aconitase and possibly synthesis of glutamate (129). The fact that iron plays a critical role in the regulation of xCT in RPE was supported by studies in HFE knock-out mice (HFE -/ -), a model for the human iron overload disorder haemochromatosis.…”
Section: Studies Of System X Cmentioning
confidence: 99%
“…It has been proposed that in the lens cortex, xCT works with EAAT4 to accumulate cystine for the synthesis of GSH; whereas in the lens nucleus (a site where GSH is not synthesized), xCT may work with ASCT2 to accumulate cystine, which when reduced to cysteine may itself act as a low-molecular-mass antioxidant (146)(147)(148). Interestingly, Lall and co-workers performed immunohistochemical localization studies of xCT in the canine lens using the same antiserum and reported that the highest levels of xCT were in lens cortical fibers, but found no xCT in the nuclear region of the lens (129). In this same study, it was shown that iron, which is known to induce oxidative damage, regulates the activity of system x c -in the lens.…”
Section: Studies Of System X Cmentioning
confidence: 99%